1999
DOI: 10.1111/j.1600-0536.1999.tb05998.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to thimerosal in atopic children

Abstract: Thimerosal is an organic mercurial compound widely used as a preservative in vaccines, eyedrops, and contact lens cleaning and storage solutions. 5 infants, 2 female and 3 male, ranging in age from 7 to 28 months and affected by atopic dermatitis (AD) diagnosed according to the Hanifin and Rajka criteria, experienced an exacerbation of their clinical condition 2-10 days after mandatory vaccinations with vaccines containing thimerosal. Cutaneous lesions of nummular eczema appeared on the trunk, limbs and face. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Testing for thimerosal sensitivity is done using the patch method. Interestingly, in one study, five infants were reported to have worsening of their atopic dermatitis after injections with thimerosal-containing vaccine, yet the infants were able to complete the recommended vaccination schedule without any serious reactions [10].…”
Section: Allergic Reactions To Preservativesmentioning
confidence: 99%
“…Testing for thimerosal sensitivity is done using the patch method. Interestingly, in one study, five infants were reported to have worsening of their atopic dermatitis after injections with thimerosal-containing vaccine, yet the infants were able to complete the recommended vaccination schedule without any serious reactions [10].…”
Section: Allergic Reactions To Preservativesmentioning
confidence: 99%
“…Thimerosal is found in contact lens solutions and vaccines (363). Antiperspirants containing zirconium can cause granulomas to form.…”
Section: Contact Dermatitidesmentioning
confidence: 99%
“…The mercury or thiosalicylate components of thiomersal may produce hypersensitivity reactions 11 . Reactions are uncommon, even in those with sensitisation, and serious reactions are rare.…”
Section: Preservativesmentioning
confidence: 99%